São Luiz Craton and Gurupi Belt (Brazil): possible links with the West African Craton and surrounding Pan-African belts - KLEIN, Evandro Luiz (2008)
The São Luís Craton and the Palaeoproterozoic basement rocks of the Neoproterozoic Gurupi Belt in northern Brazil are part of an orogen having an early accretionary phase at 2240–2150 Ma and a late collisional phase at 2080+20 Ma. Geological, geochronological and isotopic evidence, along with palaeogeographic reconstructions, strongly suggest that these Brazilian terrains were contiguous with the West African Craton in Palaeoproterozoic times, and that this landmass apparently survived subsequent continental break-up until its incorporation in Rodinia. The Gurupi Belt is an orogen developed in the southern margin of the West African–São Luís Craton at c. 750–550 Ma, after the break up of Rodinia. Factors such as present-day and possible past geographical positions, the timing of a few well-characterized events, the structural polarity and internal structure of the belt, in addition to other indirect evidence, all favour correlation between the Gurupi Belt and other Brasiliano/Pan-African belts, especially the Médio Coreau domain of the Borborema Province and the Trans-Saharan Belt of Africa, despite the lack of proven physical links between them. These Neoproterozoic belts are part of the branched system of orogens associated with amalgamation of the Amazonian, West Africa–São Luís, São Francisco and other cratons and minor continental blocks into the West Gondwana supercontinent